2008
DOI: 10.2146/ajhp070261
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone for schizophrenia

Abstract: Paliperidone does not offer any clear advantage over other atypical antipsychotics with a similar receptor-binding profile, such as risperidone and ziprasidone. Nevertheless, a few investigations have demonstrated the ability of paliperidone to produce significant improvements in psychopathology, functioning, and relapse when compared with placebo. Based on limited studies, the frequency of adverse effects, except for hyperprolactinemia, appears to favor paliperidone over risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 36 publications
0
35
1
4
Order By: Relevance
“…Paliperidone is the 9-hydroxy metabolite of risperidone and a benzisoxazole derivate with highest concentrations present in the cortex and striatum (Karlsson et al 2005). Additionally, paliperidone shares comparable pharmacodynamic properties and antagonistic profile with risperidone (Mannens et al 1993;Citrome 2007;Dolder et al 2008). For example, paliperidone and risperidone have similar affinities for serotonin-2A (5-HT 2A ) receptor subtype with inhibition constants (K i ) of 0.25 and 0.16, respectively, and with dopamine-2 (D 2 ) receptor subtype with K i of 4.0 (paliperidone) and 3.3 (risperidone; Schotte et al 1996;Dolder et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paliperidone is the 9-hydroxy metabolite of risperidone and a benzisoxazole derivate with highest concentrations present in the cortex and striatum (Karlsson et al 2005). Additionally, paliperidone shares comparable pharmacodynamic properties and antagonistic profile with risperidone (Mannens et al 1993;Citrome 2007;Dolder et al 2008). For example, paliperidone and risperidone have similar affinities for serotonin-2A (5-HT 2A ) receptor subtype with inhibition constants (K i ) of 0.25 and 0.16, respectively, and with dopamine-2 (D 2 ) receptor subtype with K i of 4.0 (paliperidone) and 3.3 (risperidone; Schotte et al 1996;Dolder et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, paliperidone shares comparable pharmacodynamic properties and antagonistic profile with risperidone (Mannens et al 1993;Citrome 2007;Dolder et al 2008). For example, paliperidone and risperidone have similar affinities for serotonin-2A (5-HT 2A ) receptor subtype with inhibition constants (K i ) of 0.25 and 0.16, respectively, and with dopamine-2 (D 2 ) receptor subtype with K i of 4.0 (paliperidone) and 3.3 (risperidone; Schotte et al 1996;Dolder et al 2008). Furthermore, 5-HT 2A /D 2 affinity ratio has been shown to be very similar between paliperidone (K i =0.06) and risperidone (K i =0.05; Schotte et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used for schizophrenia and schizoaffective disorder. Paliperidone (9-OH-risperidone) is a receptor monoaminergic antagonist that exhibits the characteristic dopamine type 2 (D2) and serotonin (5-hydroxytryptamine 5-HT) type 2A (5-HT2A) antagonism of antipsychotic drugs 4,5 . An extensive literature survey is carried out and very few spectrophotometric 6 methods were found so far.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, interest has turned to the active metabolites of atypical antipsychotic drugs in the hope that they might have increased efficacy over the parent drug and a reduced incidence of side effects. The active metabolite of risperidone, 9-OH-risperidone (paliperidone [Invega®]) from Janssen Pharmaceuticals, has recently met FDA approval and is being used clinically for the treatment of schizophrenia in the US (Dlugosz and Nasrallah 2007;Dolder et al 2008). The active metabolite for clozapine, N-desmethylclozapine (Li et al 2005), was being developed by Acadia Pharmaceuticals, as ACP-104, for the treatment of schizophrenia; however, a recent press release (Reuters, June 16 2008) reported that ACP-104 did not display antipsychotic efficacy compared to placebo in Phase IIb clinical trials.…”
Section: Introductionmentioning
confidence: 99%